Dermatoscopy of basal cell carcinoma: Morphologic variability of global and local features and accuracy of diagnosis - Altamura, Davide; Menzies, Scott W.; Argenziano, Giuseppe; Zalaudek, Iris; Soyer, H. Peter; Sera, Francesco; Avramidis, Michelle; DeAmbrosis, Kathryn; Fargnoli, Maria Concetta; Peris, Ketty (Journal of the American Academy of Dermatology, 2010)
Early detection of basal cell carcinoma (BCC) is crucial to reduce the morbidity of this tumor. We sought to investigate the variability and diagnostic significance of dermatoscopic features of BCCs. We conducted retrospective dermatoscopic analysis of 609 BCCs and 200 melanocytic and nonmelanocytic lesions, and assessment of interrater reliability of dermatoscopic BCC criteria. Lesions included nonpigmented (15.1%), lightly pigmented (33.2%), pigmented (42.7%), and heavily pigmented (9%) BCCs. Classic BCC patterns including arborizing telangiectasia (57.1%), blue/gray ovoid nests (47.5%), ulceration (39.2%), multiple blue/gray globules (26.1%), leaflike areas (15.9%), and spoke-wheel areas (9%) were significantly increased in pigmented BCCs compared with nonpigmented and heavily pigmented BCCs (P = .0001). Among nonclassic BCC patterns, we detected short fine superficial telangiectasia (10%) and multiple small erosions (8.5%), and described two new patterns named “concentric structures” (7.6%) and “multiple in-focus blue/gray dots” (5.1%). Dermatoscopic features suggestive of melanocytic lesions (eg, multiple brown to black dots/globules, blue/white veillike structures, and nonarborizing vessels) were observed in 40.6% BCCs and significantly increased in heavily pigmented BCCs (P < .0001). Expert observers provided an accurate (sensitivity: 97%) and reliable (K: 87%) dermatoscopic diagnosis of BCC, although a significant difference in terms of specificity (P = .0002) and positive predictive value (P = .0004) was found. Arborizing telangiectasia, leaflike areas, and large blue/gray ovoid nests represented reliable and robust diagnostic parameters. The study was retrospective. BCCs show a large spectrum of global and local dermatoscopic features; heavily pigmented BCCs show the most challenging combinations of dermatoscopic features.